Development of purification and crystallization of yam sugar - Muhamad Alexander Hamid Ho, Ridzuan (Universiti Malaysia Sarawak (UNIMAS), 2013)
This project is to produce crystal yam (Colocasia esculenla (L.) Schott.) sugar from. The main objective of this study is to compare the glucose obtained from two different varieties of yam (variety A and variety B). The different varieties of yam were obtained from both market (variety A) and field (variety B) independently, and the starch was hydrolyzed into glucose. Enzymatic hydrolysis was completed in 2 stages which are liquefaction (using Termamyl-120L) and saccharification (using AMG enzyme). The crystallized glucose was produced by purifYing the HYS using PAC by either gravitational forces or peristaltic pump followed with crystallizing the PYS using either boiling, oven drying, or refrigerator cooling. The result on purifYing of glucose show that, higher glucose recovery rate was able to be achieved by using gravitational force at glucose recovery rate of 80.8% as compared to using of peristaltic pump at glucose recovery rate of 71.7%. In the crystallization process, only refrigerator drying showed promising result in attempt to crystallize the glucose by crystallizing within 8 days. The glucose recovery rate of variety A was higher as compared to variety B with 95.72% and 61 .83%, respectively. There was about 251.13g of glucose hydrolyzed from I kg of variety A and variety B only able to produce 129.50g of glucose. The total mass of fresh yam required in producing I kg of sugar for variety A and variety B was 12.29kg and 19.04kg, respectively.